Dampak Kebijakan Pembatasan Sosial Berskala Besar Terhadap Komunitas Ojek Online di Palembang - Nevsia Carlina; Alamsyah Alamsyah; Zailani Surya Marpaung (Administratio, 2022)
This research was trying to analyze how the Impact of Large-scale Social Restriction Policies on the Social Capital of Online Taxi Community at the West Musiraya Intersection (SIMBAT) in Palembang City. This research method is interpretative qualitative. The research data was from key informants who chosen by purposive, archives, books, documentation, regulations, social media, and websites. The research data was collected with an in-depth interview, observation, documentation, and analyzed using ATLAS.ti 9 software. The research results showing that PSBB policy causes a drop in income drivers makes powering the social capital of the Community of SIMBAT. The authors recommend to before making a policy to resolve COVID-19, the government must be considered impact and risk will soon for target groups. The Government must be prepared a solution if occur what undesirable impact.